A pattern of poisoning in children- an experience from a teaching hospital in southern India - Dr. Vijayalakshmi P; Dr. Shreeshail V. Benakanal; Dr. Ravindra B. Patil; Dr. Manoj GM; Dr. R. Vikram S. Kumar (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Poisoning in children is an important Paediatric emergency and is a worldwide problem. It is a common and preventable cause of morbidity and mortality in children.Objectives: The aim of this study was to determine the profile and outcome of children less than 13 years admitted to the Paediatric department presenting with acute poisoning at a Teaching district hospital in southern Karnataka.Methods: Prospectively, 134 acute poisoning cases, admitted to Paediatric intensive care, SIMS Shivamogga from November 2018 to May 2019 were included in this study.Results: During the study period, 134 patients presented with acute poisoning. The incidence of poisoning in Paediatric patients was 2.84%. The median age of our patients was 5.2 years (range 0.75-12 years). The male to female ratio was 1.58:1. Animal bites (27.61%), Petroleum products (26.87%), Household chemicals (15.67%), Drugs (11.19%), Poisonous plant derivatives (8.96%) and Insecticides (6.72%) were the agents most frequently implicated. Almost all (98.41%) cases in 1 to 5 years age group were accidental in nature, whereas in the >10 years age group, the majority (71.43%) were suicidal. Thirteen patients (9.7%) remained asymptomatic. The specific antidote was given to 19 (14.18%) patients. Three patients (2 snake bite and 1 rodenticide child) died. The mean duration of hospital stay was 4.49 days (range was 1 day to 22 days).Conclusions: Accidental poisoning was common in children below 5 years of age. Minimal age of suicidal poisoning was 8 years. The most common agent implicated was a snake bite.